2012
DOI: 10.1016/j.molcel.2012.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Functional Annotation of Dual-Specificity Protein- and Lipid-Binding Modules that Regulate Protein Interactions

Abstract: Emerging evidence indicates that membrane lipids regulate protein networking by directly interacting with protein-interaction domains (PIDs). As a pilot study to identify and functionally annodate lipid-binding PIDs on a genomic scale, we performed experimental and computational studies of PDZ domains. Characterization of 70 PDZ domains showed that 40% had submicromolar membrane affinity. Using a computational model built from these data, we predicted the membrane binding properties of 2000 PDZ domains from 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
61
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 41 publications
3
61
0
Order By: Relevance
“…11A (left) show the time courses of binding to the lipid vesicles at the indicated domain concentrations. The sensorgrams show that there was essentially no significant binding of the PDZ3 domain, as reported previously (36), whereas there was a dose-dependent binding of PDZ4. Fig.…”
Section: Analysis Of the Membrane Binding Activity Of Pdz4 Using Sprsupporting
confidence: 83%
See 4 more Smart Citations
“…11A (left) show the time courses of binding to the lipid vesicles at the indicated domain concentrations. The sensorgrams show that there was essentially no significant binding of the PDZ3 domain, as reported previously (36), whereas there was a dose-dependent binding of PDZ4. Fig.…”
Section: Analysis Of the Membrane Binding Activity Of Pdz4 Using Sprsupporting
confidence: 83%
“…We thus measured the binding of PDZ4 and other PDZ domains from PDZK1 to vesicles whose lipid composition mimics that of the inner leaflet of the plasma membrane of mammalian cells (50). We previously reported that PDZ1, PDZ2, and PDZ3 domains from PDZK1 do not individually bind to such vesicles (36). Here, we measured the binding of individual recombinant PDZ4 and PDZ3 domains to plasma membrane mimetic vesicles.…”
Section: Analysis Of the Membrane Binding Activity Of Pdz4 Using Sprmentioning
confidence: 97%
See 3 more Smart Citations